1988
DOI: 10.1021/jm00400a022
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity profile of a series of novel triazoloquinazoline adenosine antagonists

Abstract: During a search for benzodiazepine receptor modulators, a highly potent adenosine antagonist (CGS 15943) was discovered. The compound was defined as a resonance-stabilized hybrid of the canonical structures 9-chloro-2-(2-furyl)[1,2,4]triazolo[1,5-c]quinazolin-5-amine (2a) and 9-chloro-2-(2-furyl)-5,6-dihydro[1,2,4]triazolo[1,5-c]-quinazolin- 5-imine (2b). Spectroscopic evidence and chemical reactivity in polar media favor the amine form 2a as the major contributor of the two canonical structures. The synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 3 publications
(3 reference statements)
2
116
0
Order By: Relevance
“…Initially it was found that 2-substituted analogs such as 2-chloroadenosine (14, CADO) and 2-chloro-N 6 -cyclopentyladenosine (11, CCPA) were relatively well tolerated at A 3 receptors (26). For example, CPA (12) and CCPA (11) are equipotent at rat A 3 receptors (Table I). The C2-modification was also compatible or additive with A 3 potency-enhancing modifications at other sites on the adenosine molecule.…”
Section: Ligand Development Selective a 3 Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially it was found that 2-substituted analogs such as 2-chloroadenosine (14, CADO) and 2-chloro-N 6 -cyclopentyladenosine (11, CCPA) were relatively well tolerated at A 3 receptors (26). For example, CPA (12) and CCPA (11) are equipotent at rat A 3 receptors (Table I). The C2-modification was also compatible or additive with A 3 potency-enhancing modifications at other sites on the adenosine molecule.…”
Section: Ligand Development Selective a 3 Agonistsmentioning
confidence: 99%
“…Adenosine agonists, which are almost exclusively derivatives of adenosine (1), have been sought as potential hypotensive (2), antipsychotic (3,4), antiarrhythmic (5), antilipolytic (thus antidiabetic, 6) and cerebroprotective (7)(8)(9)(10) agents. Adenosine antagonists, of which xanthines and a number of fused heterocyclic ring systems are representative (1), have been under development as antiasthmatic (11), antidepressant (12), antiarrhythmic (13), renal protective (14,15), antiparkinson (16) and cognitive enhancing (17)(18)(19) drugs. In spite of the massive effort to develop selective ligands, a number of agents that initially looked promising did not survive clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, CGS 15943A, 14 ( Fig. 1) [33], was targeted in aerosol form as an antiasthmatic but failed in development due to skin irritation. A series of triazoloquinoxalines from Pfizer, which for a time were in clinical trials as antidepressants, were later found to include some A 2 -receptor selective adenosine antagonists [34], such as CP 66,713 (15).…”
Section: Adenosine Antagonistsmentioning
confidence: 99%
“…7 The synthesis of such compounds has been the subject of several reviews which demonstrate the high importance of this class of compounds. [8][9][10][11][12][13] Considering the importance of these compounds, many methods for the synthesis of these derivatives have been reported successively. The conventional synthesis imidazoles, 17 1,3-oxathioles 18 and condensed imidazolo and thiazolo derivatives, 19 because of their multifunctional structure.…”
Section: Introductionmentioning
confidence: 99%